Pathophysiological and hygienic aspects of hand-arm vibration. - Pyykko, I.; Starck, Jukka (Scandinavian Journal of Work, Environment & Health, 1986)
A review of current knowledge on the pathophysiological and hygienic aspects of the hand-arm vibration syndrome is given. Hemodynamic measurements indicate that the primary factor in vibration-induced white finger is an increase in the peripheral resistance of finger circulation that is present after local and general cooling. The reason for this increase is not known, but it is postulated that an excessive affinity of vasoactive substances for the efferent receptors exists, this affinity being potentiated during local cooling of the digits. So far, the hygienic rating of hazardous vibration in individual work phases is of limited value in diagnosing possible cases, but this rating does provide guidelines for general risk assessment. A consideration of several factors, eg, intermittency of the work, duration of daily exposure, impact of vibration, individual physiological responses, climate, etc, might improve the accuracy of the rating, but the influence of these factors on the development of the vibration syndrome is still poorly understood. Of various preventive measures, only those that significantly reduce vibration will be beneficial in the long run.